Why poverty persists in India: a framework for understanding the India economy - Eswaran, Mukesh; Kotwal, Ashok (New Delhi, 2010)
After fifty years of development, mass poverty still persists in India. This analysis attempts to bring out how various sectors of the economy impinge on the development process. The authors show that two key features to the elimination of poverty in India are transferring labor from agriculture to industry and growth in agricultural productivity. They argue that industrial progress cannot benefit the poor in the absence of progress in the agricultural sector. They also show that by exporting industrial goods, the labor force employed in agriculture can be reduced and the poor in India would be made better off. Finally, they argue that India's industrial policy from Independence until very recently was designed to stifle entrepreneurship and undermine technical advancement.
Keywords: Poverty-India